Fermentation kinetics (in vitro) of Leucaena leucocephala, Gliricidia sepium and Calliandra callothyrsus leaves (3) the pattern of gas production, organic matter degradation, pH, NH3 and VFA concentration; estimated CH4 and microbial biomass production - Y Widiawati; M Winugroho; E Teleni; A Thalib (Jurnal Ilmu Ternak dan Veteriner, 2007)
In high protein feeds, plant proteins may be shielded from degradation in the rumen by lignification of the cell wall or because of the present of plant secondary compounds e.g. tannin, which is present in most of the leguminous trees/shrubs. Thus it might have an effect on organic matter degradation and the pattern of other end product of rumen microbial fermentation (VFA, NH3, microbial cell, CH4 and total gas). The in vitro method was used to determine the organic matter degradation and the pattern of rumen fermentation end product of high protein feeds, namely Leucaena leucocephala, Gliricida sepium and Calliandra calothyrsus. The results shows that Gliricidia has the highest amount of OM degraded (505 mg); microbial cell and NH3 produced (2676 g and 1.91 mmol/100 mL) than followed by Leucaena (423 mg; 2656 g; 1.61 mmol/100 mL) and Calliandra (340 mg; 2644 g; 1.61 mmol/100mL), but Gliricidia produced the lowest amount of gas total and CH4 (0.192 mL and 0.07 mole per mg OM deraded) then Leucaena (0.249 mL and 0.097 mole per mg OM deraded) and Callliandra (0.196 mL and 0.126 mole per mg OM deraded). In conclusion, Gliricidia is more efficient in term of using the dietary energy for the animals’ production compared to the Leucaena and Calliandra. Key Words: Legumes Tree, Organic Matter, NH3, VFA, CH4, Microbial Cell